(untitled) (Research, Society and Development, 2020)
The objectives of this work were to evaluate the genetic variability of bean lineages in relation to phosphorus accumulation in plant tissues and yield, in addition to identifying efficient bean lineages in the use of phosphorus and responsive to the application of phosphorus in the crop environment. Work was carried out at Plant Science Department of the Federal University of Santa Maria. Concentrations of phosphorus in the nutrient solution between 1.33 and 1.84 mmol L-1 provide higher dry mass of pods, grains, number of grains and grain yield for the cultivars Pérola and IPR88 Uirapurú in the growing seasons autumn-winter and spring-summer. Concentrations between 1.37 and 1.96 mmol L-1 have the highest values of phosphorus in plant tissues, grain yield and phytic acid. Characteristics dry matter of leaves, stem and pods in pod filling, dry matter of grains on maturation, number of grains, number of pods and phosphorus concentration in plant tissues at the pod filling stage are promising because it allows for indirect selection. The nutritional value of leaves in young plants, for phosphorus, equivalent to that of grains. There is genetic variability among the bean lineages studied, for the production of dry mass, yield and accumulation of phosphorus in the tissues. Lineage L 2527 showed to be efficient and responsive to the use of phosphorus for the shoot of the plant. Lineage L 2225 showed to be efficient in the use of phosphorus in shoot, grains and grain production, besides maintaining this characteristic in the two growing seasons.